2020
DOI: 10.11591/eei.v9i5.2055
|View full text |Cite
|
Sign up to set email alerts
|

Design of a wideband strip helical antenna for 5G applications

Abstract: This paper presents the design of wideband strip helical antenna for 5G Application. The strip helical antenna is designed for 5G and wideband applications that provide a wide bandwidth and circular polarization. The helical antenna is planned on at 5.8 GHz frequency by using Teflon material. The new designed strip is printed on a substrate then rolled into a helix shape to achieve circular polarization without an impedance matching and that the proposed antenna can be used for potential applications in wideba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The formation of the fixed zeros of the electric field at a finite distance from the system of radiators carried out by selecting the amplitude and phase difference of their currents [25]. The effectiveness of interference suppression lies in its main property: if two signals of the same amplitude interfere, then when adding in phase at a given point, the power rises to 3dB, and in antiphase it is suppressed to minus infinity dB [26], [27].…”
Section: Research Methods 21 Broblem Formulationmentioning
confidence: 99%
“…The formation of the fixed zeros of the electric field at a finite distance from the system of radiators carried out by selecting the amplitude and phase difference of their currents [25]. The effectiveness of interference suppression lies in its main property: if two signals of the same amplitude interfere, then when adding in phase at a given point, the power rises to 3dB, and in antiphase it is suppressed to minus infinity dB [26], [27].…”
Section: Research Methods 21 Broblem Formulationmentioning
confidence: 99%
“…The direction of the beam scanning is directed by changing the operation frequency. The equation of the direct beam steering of the leaky-wave antenna is assumed by [9], [10]. Where θ(f) is the broadside angle, ko is the wavenumber, and β is defined as the phase constant.…”
Section: Introductionmentioning
confidence: 99%
“…Our use of devices such as televisions, computers, laptops, e-readers and cell phones has increased exponentially over the past few decades (Tang et al, 2016a). The calculated model for charging an electronic device from the ambient EM waves is unusual in the literature (Tang et al, 2016b;Zeain et al, 2020;Guo et al, 2016;Kar et al, 2021;Dai et al, 2016;Kindl et al, 2020;Jiang et al, 2012;Beh et al, 2014;Zeng et al, 2017), despite its importance for coverage forecasts. Using the previous approaches, induced voltage was so low.…”
Section: Introductionmentioning
confidence: 99%
“…Implementing this model, charging problems can be reduced. Zeain et al (2020), the authors suggested a striphelical antenna with a parasitic circular patch for circular polarization. Two nearby Circularly Polarized (CP) resonances were created and a broad Axial Ratio (AR) bandwidth was obtained by combining the strip-helix and the parasitic patch.…”
Section: Introductionmentioning
confidence: 99%